Lithium nickel manganese oxide positive electrode material as well as preparation method and application thereof
By forming a cladding layer on the nickel-manganate positive electrode material with coral structure, the problem of low first-effect and rate performance of nickel-manganate positive electrode material is solved by using Al, Ti, Zr and Nb materials and surfactant. , significantly improves its electrochemical properties and stability.
Patent Information
- Application Number
- CN202411139107.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-20
Smart Images

Figure CN119170763A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of lithium battery technology, and in particular relates to a lithium nickel manganese oxide positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium nickel manganese oxide with layered oxide structure is an important branch of the positive electrode materials of lithium-ion batteries. As a cobalt-free positive electrode material, its low cost characteristics are highly anticipated by the market. The basic skeleton structure of lithium nickel manganese oxide with layered oxide structure is similar to that of the current lithium nickel cobalt manganese oxide positive electrode materials (LiNi x Co y Mn z O2, x+y+z≤1), that is, a two-dimensional space framework composed of alternating lithium layers and transition metal layers provides an effective channel for the rapid extraction and insertion of lithium ions, thus showing excellent electrochemical performance during the battery charge and discharge process. 0.5 Mn 1.5 Compared with O4, the voltage platform of layered nickel manganese oxide is slightly lower, but its theoretical gram capacity can reach more than 270mAh / g. x Mn y O2), manganese accounts for a high proportion, and the cost of raw materials will be reduced by more than 30% compared with NCM materials. However, lithium nickel manganese oxide with layered oxide structure also faces some challenges in practical applications. The lack of Co element reduces the cost but also loses the improvement in rate performance brought by cobalt. The lack of cobalt will also improve the thermal safety of the material to a certain extent, but it will also cause the nickel-lithium mixing of the material to be more serious. Therefore, compared with conventional ternary materials, layered lithium nickel manganese oxide will face greater challenges in rate.
[0003] The diffusion efficiency of lithium ions in the battery cell is mainly affected by factors such as the diffusion barrier of the crystal structure, the diffusion path, the reaction area and the solvation efficiency. Among them, the diffusion barrier is mainly reduced by bulk doping; the optimization of the diffusion path and the reaction area is mainly achieved by regulating the particle structure (particle size and specific surface area, etc.); the solvation efficiency needs to be improved by the electrolyte and the electrolyte. Existing patents pay less attention to the surface structure of lithium-ion layered nickel manganese oxide positive electrode materials and the rate performance of batteries, mainly focusing on the spinel structure, but the spinel structure is mainly limited by the development of high-voltage electrolytes. The prior art reports a composite layered nickel manganese oxide positive electrode material and a preparation method thereof. The composite material includes a matrix material and a surface-coated hydrophobic organic matter. The coating material can protect the interface and reduce residual alkali, but the composition elements of the coating material are complex and require multiple elements to work together, and there is no mention of the content on the grain structure. The prior art also discloses the use of a surface coating method to improve the stability of the material, but there is no structural description of the rate performance improvement. Summary of the invention
[0004] The purpose of the present application is to provide a lithium nickel manganese oxide positive electrode material and a preparation method and application thereof, aiming to solve the problems of low first efficiency, low rate performance and poor stability of the lithium nickel manganese oxide positive electrode material.
[0005] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0006] In a first aspect, the present application provides a lithium nickel manganese oxide positive electrode material, which includes a lithium nickel manganese oxide layered oxide and a coating layer coated on the surface of the lithium nickel manganese oxide layered oxide, wherein the coating layer has a coral-like structure; the material in the coating layer is selected from one or more of Al, Ti, Zr and Nb.
[0007] According to some embodiments of the lithium nickel manganese oxide positive electrode material of the present application, the general chemical formula of the lithium nickel manganese oxide positive electrode material is Li a Ni 1-x-y Mn x M y O2, wherein: 0.95≤a≤1.1, 0.05≤x≤0.5, 0.01≤y≤0.1; M is selected from one or more of Al, Ti, Zr, and Nb.
[0008] According to some embodiments of the nickel manganese oxide positive electrode material of the present application, the specific surface area of the nickel manganese oxide positive electrode material is 0.4 m 2 / g-1.5m 2 / g.
[0009] According to some embodiments of the lithium nickel manganese oxide positive electrode material described in the present application, D50 of the lithium nickel manganese oxide positive electrode material is 1.5 μm-5.5 μm.
[0010] According to some embodiments of the lithium nickel manganese oxide positive electrode material described in the present application, the diameter pitch of the lithium nickel manganese oxide positive electrode material is 1.0-2.0.
[0011] According to some embodiments of the lithium nickel manganese oxide positive electrode material described in the present application, the thickness of the coating layer contained in the lithium nickel manganese oxide positive electrode material is 0.1 nm-10 nm.
[0012] In a second aspect, a method for preparing a lithium nickel manganese oxide positive electrode material is provided, comprising the following steps:
[0013] The nickel manganese oxide precursor is mixed with a lithium source and sintered for the first time to obtain a nickel manganese oxide lithium sintered material;
[0014] The lithium nickel manganese oxide sintering material is mixed with a surfactant and sintered for a second time to obtain the lithium nickel manganese oxide positive electrode material.
[0015] According to some embodiments of the preparation method described in the present application, the surfactant is selected from one or more of ammonium niobium oxalate, niobium oxide, aluminum oxide, zirconium oxide, and titanium oxide.
[0016] According to some embodiments of the preparation method described in the present application, the mass ratio of the lithium nickel manganese oxide sintered material to the surfactant is 100:(1-7).
[0017] According to some embodiments of the preparation method described in the present application, the chemical formula of the nickel manganese oxide precursor is Ni 1-x Mn x O2, where 0.05≤x≤0.5.
[0018] According to some embodiments of the preparation method described in this application, the specific surface area of the nickel manganese oxide precursor is 5m 2 / g-15m 2 / g.
[0019] According to some embodiments of the preparation method described in the present application, the morphology of the nickel manganese oxide precursor includes nanoscale spherical particles and / or nanoscale spherical-like particles.
[0020] According to some embodiments of the preparation method described in the present application, the spherical particles are elliptical particles.
[0021] According to some embodiments of the preparation method described in the present application, the nickel manganese oxide precursor D50 is 3 μm-4 μm.
[0022] According to some embodiments of the preparation method described in the present application, D50 of the lithium source is 5 μm-10 μm.
[0023] According to some embodiments of the preparation method described in the present application, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium sulfate, and lithium nitrate.
[0024] According to some embodiments of the preparation method described in the present application, the molar ratio of the nickel manganese oxide precursor to the lithium source is 1:(1.02-1.12).
[0025] According to some embodiments of the preparation method described in the present application, the first sintering is carried out under the condition of introducing air, and the flow rate of the introduced air is 2L / min-5L / min.
[0026] According to some embodiments of the preparation method described in the present application, the temperature of the first sintering is 900° C.-950° C., and the time of the first sintering is 12 h-20 h.
[0027] According to some embodiments of the preparation method described in the present application, the first sintering is carried out under the condition of introducing air, and the flow rate of the introduced air is 3 L / min.
[0028] According to some embodiments of the preparation method described in the present application, the first sintering is performed by heating the temperature to 900°C-950°C at a heating rate of 3°C / min-8°C / min.
[0029] According to some embodiments of the preparation method described in this application, the chemical formula of the lithium nickel manganese oxide sintered material is Li a Ni 1-x Mn x O2, where 0.95≤a≤1.1, 0.05≤x≤0.5.
[0030] According to some embodiments of the preparation method described in the present application, D50 of the lithium nickel manganese oxide sintered material is 3 μm-10 μm.
[0031] According to some embodiments of the preparation method described in the present application, in step (2), the second sintering is performed under the condition of passing air.
[0032] According to some embodiments of the preparation method described in the present application, the flow rate of the introduced air is 2L / min-5L / min.
[0033] According to some embodiments of the preparation method described in the present application, the temperature of the second sintering is 450° C.-650° C., and the time of the second sintering is 3 h-8 h.
[0034] According to some embodiments of the preparation method described in the present application, the flow rate of the introduced air is 3 L / min.
[0035] According to some embodiments of the preparation method described in the present application, the second sintering is performed by heating the temperature to 450°C-650°C at a heating rate of 3°C / min-8°C / min.
[0036] In a third aspect, a lithium-ion battery is provided, comprising the lithium nickel manganese oxide positive electrode material described in the first aspect of the present application or the lithium nickel manganese oxide positive electrode material obtained by the preparation method described in the second aspect of the present application.
[0037] In a fourth aspect, an electrical device is provided, wherein the electrical device comprises the lithium-ion battery described in the fourth aspect of the present application.
[0038] Compared with the prior art, the beneficial effects of this application are:
[0039] 1. In the lithium nickel manganese oxide positive electrode material described in the present application, on the one hand, the material of the coating layer is selected from one or more of Al, Ti, Zr and Nb, which can act as a physical barrier between the positive electrode material and the electrolyte, stabilize the interface, block the dissolution of metal ions and effectively prevent the collapse of the surface structure of the active material, and has the advantages of improving electronic conductivity, improving stability, and expanding Li + The role of embedding / ejecting channels and reducing the degree of cation mixing, thereby improving the electrochemical performance of the positive electrode material. On the other hand, the coating layer has a coral-like structure. The coral-like concave-convex structure can effectively increase the adsorption area of lithium ions, reduce the interface impedance, make lithium ions easy to transmit at the interface, enhance the kinetic characteristics of lithium ions, and improve the rate performance of nickel manganese oxide lithium positive electrode materials.
[0040] 2. In the preparation process of the lithium nickel manganese oxide positive electrode material described in the present application, the layered oxide positive electrode material and the surfactant are fused with each other and then heat treated to prepare a layered oxide lithium battery positive electrode material with a highly active surface, which makes it easy for lithium ions to be transmitted at the interface, can significantly improve the first efficiency of the material, reduce the growth rate of DCR during the cycle, and improve its cycle stability.
[0041] 3. The lithium-ion battery described in the present application contains the lithium nickel manganese oxide positive electrode material described in the first aspect or the second aspect of the present application, so that the lithium-ion battery has a higher initial efficiency and relatively high cycle stability.
[0042] 4. The electrical device described in the present application contains the lithium nickel manganese oxide positive electrode material described in the first aspect or the second aspect of the present application, so that the electrical device has a higher initial efficiency and relatively high cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0044] Figure 1 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 1 of the present application at a magnification of 20K;
[0045] Figure 2 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 1 of the present application at a magnification of 30K;
[0046] Figure 3 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 1 of the present application at a magnification of 40K;
[0047] Figure 4A graph showing the surface energy spectrum test result of any point of the lithium nickel manganese oxide positive electrode material prepared in Example 1 of the present application;
[0048] Figure 5 The nickel manganese oxide positive electrode material prepared in Example 1 of the present application is Figure 4 Surface energy spectrum test results at different points;
[0049] Figure 6 This is a result diagram of the surface energy spectrum scanning test (Nb element) of the lithium nickel manganese oxide positive electrode material prepared in Example 1 of the present application;
[0050] Figure 7 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 2 of the present application at a magnification of 20K;
[0051] Figure 8 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 3 of the present application at a magnification of 20K;
[0052] Fig. 9 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 4 of the present application at a magnification of 20K;
[0053] Fig.10 This is a SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 5 of the present application at a magnification of 20K. DETAILED DESCRIPTION
[0054] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0055] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0056] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0057] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0058] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0059] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0060] A first aspect of an embodiment of the present application provides a lithium nickel manganese oxide positive electrode material, the positive electrode material comprising a lithium nickel manganese oxide layered oxide and a coating layer coated on the surface of the lithium nickel manganese oxide layered oxide, the coating layer presenting a coral-like structure; the material in the coating layer is selected from one or more of Al, Ti, Zr and Nb.
[0061] The coral-like structure may be a uniformly distributed gully structure, and the surface area of the gully accounts for 27%-33% of the surface area of the lithium nickel manganese oxide particles.
[0062] The material in the coating layer can act as a physical barrier between the positive electrode material and the electrolyte, stabilize the interface, block the dissolution of metal ions and effectively prevent the collapse of the surface structure of the active material, and has the advantages of improving electronic conductivity, improving stability, and expanding Li + The coral-like concave-convex structure can effectively increase the adsorption area of lithium ions, reduce the interface impedance, make lithium ions easy to transfer at the interface, enhance the kinetic characteristics of lithium ions, and improve the rate performance of lithium nickel manganese oxide cathode materials.
[0063] In some embodiments, the material in the coating layer may be Al or Ti; in some embodiments, the material in the coating layer may also be Zr or Nb; in some embodiments, the material in the coating layer may also be Al and Ti; in some embodiments, the material in the coating layer may also be Ti, Zr and Nb; in some embodiments, the material in the coating layer may also be Al, Ti, Zr and Nb.
[0064] In some embodiments, the chemical formula of the lithium nickel manganese oxide positive electrode material is Li a Ni 1-x-y Mn x M y O2, wherein: 0.95≤a≤1.1, 0.05≤x≤0.5, 0.01≤y≤0.1; for example, a may be 0.95, 0.98, 0.99, 1.0, 1.05, 1.1, etc.; x may be 0.05, 0.07, 0.10, 0.15, 0.23, 0.25, 0.31, 0.38, 0.39, 0.43, 0.46, 0.50, etc.; y may be 0.01, 0.02, 0.04, 0.06, 0.07, 0.08, 0.09, 0.1, etc.; M may be selected from one or more of Al, Ti, Zr, and Nb. In the embodiment of the present application, controlling y within the range of 0.01-0.1 can achieve a better coating effect, and can make the coating layer uniform and thin. If the coating layer is too thick, it will hinder the diffusion of lithium during the deintercalation process, affecting its rate performance. The M material can act as a physical barrier between the positive electrode material and the electrolyte, stabilize the interface, block the dissolution of metal ions, and effectively prevent the collapse of the surface structure of the active material, which has the advantages of improving electronic conductivity, improving stability, and expanding Li + It can embed / eject channels and reduce the degree of cation mixing, thereby improving the electrochemical performance of the positive electrode material.
[0065] In some embodiments, the specific surface area of the lithium nickel manganese oxide positive electrode material is 0.4 m 2 / g-1.5m 2 / g, for example 0.4m 2 / g, 0.5m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.3m 2 / g, 1.5m 2 / g, etc.; the specific surface area of the lithium nickel manganese oxide positive electrode material in the embodiment of the present application is within this range, which can ensure that the particles will not be too agglomerated and can ensure sufficient contact with the surfactant during the subsequent coating and modification process, thereby achieving a better coating effect.
[0066] In some embodiments, the D50 of the nickel manganese oxide positive electrode material is 1.5 μm-5.5 μm, for example, 1.5 μm, 1.8 μm, 2.0 μm, 2.3 μm, 2.5 μm, 3.0 μm, 3.2 μm, 3.6 μm, 4.1 μm, 4.3 μm, 4.7 μm, 4.9 μm, 5.2 μm, 5.3 μm, 5.5 μm, etc. The D50 of the nickel manganese oxide positive electrode material in the embodiment of the present application is within this range, which can make the material in the coating layer better form a good coating layer on the positive electrode surface and achieve the expected coating effect.
[0067] In some embodiments, the diameter distance of the lithium nickel manganese oxide positive electrode material is 1.0-2.0, such as 1.0, 1.2, 1.3, 1.6, 1.8, 2.0, etc. The diameter distance of the lithium nickel manganese oxide positive electrode material indicates the distribution width of the particles, and the calculation formula is (D90-D10) / D50. The larger the diameter distance, the wider the distribution width, where D50 refers to the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. D50 is also called the median diameter or median particle size; D10 refers to a specific point in the volume distribution of the particles, that is, the particle size limit where the volume accounts for 10% of all particles. The diameter distance of the lithium nickel manganese oxide positive electrode material within this range can enable the material in the coating layer to better form a better coating layer on the positive electrode surface, thereby achieving the expected coating effect.
[0068] In some embodiments, the thickness of the coating layer contained in the lithium nickel manganese oxide positive electrode material is 0.1nm-10nm, for example, 0.1nm, 0.2nm, 0.5nm, 1.0nm, 1.3nm, 2.2nm, 3.5nm, 4.0nm, 5.0nm, 5.3nm, 5.6nm, 5.8nm, 6.7nm, 7.3nm, 7.8nm, 8.2nm, 9.1nm, 10nm, etc.
[0069] A second aspect of the present application provides a method for preparing a lithium nickel manganese oxide positive electrode material, comprising the following steps:
[0070] The nickel manganese oxide precursor is mixed with a lithium source and sintered for the first time to obtain a nickel manganese oxide lithium sintered material;
[0071] The lithium nickel manganese oxide sintering material is mixed with a surfactant and sintered for a second time to obtain a lithium nickel manganese oxide positive electrode material.
[0072] In the preparation process of the nickel manganese oxide lithium positive electrode material of the present application, the layered oxide positive electrode material and the surfactant are fused and reacted with each other, and the high-activity material in the surfactant is enriched on the surface of the positive electrode material to form a coral-like structure. The concave-convex structure of the channel can effectively increase the adsorption area of lithium ions, reduce the interface impedance, and make lithium ions easy to transmit at the interface. The lithium-ion battery assembled with the positive electrode material has a high first efficiency, a slow DCR growth during the cycle, and excellent cycle performance.
[0073] In some embodiments, the surfactant is selected from one or more of ammonium niobium oxalate, niobium oxide, aluminum oxide, zirconium oxide, and titanium oxide.
[0074] In some embodiments, the mass ratio of the nickel manganese oxide lithium sintered material to the surfactant is 100:(1-7): for example, 100:1, 100:1.7, 100:2, 100:2.6, 100:3, 100:3.6, 100:4, 100:5, 100:5.7, 100:6, 100:6.5, 100:6.8, 100:7, etc. If the amount of surfactant is too small, the effect of coating the modified positive electrode surface cannot be achieved; if the amount is too large, the coating layer will be too thick, resulting in a significant reduction in the material capacity, and may affect the lithium ion transmission. When the amount ratio is controlled in the range of 100:(1-7), a better coating effect can be achieved, and the coating layer will not be too thick.
[0075] In some embodiments, the nickel manganese oxide precursor has a general chemical formula of Ni 1-x Mn x O2, where 0.05≤x≤0.5.
[0076] In some embodiments, the specific surface area of the nickel manganese oxide precursor is 5 m 2 / g-15m 2 / g; for example 5m 2 / g, 8m 2 / g, 12m 2 / g, 13m 2 / g, 15m 2 / g, etc. When the precursor that meets the above conditions is mixed with the lithium source and sintered, the sintering is more complete and uniform, and the obtained positive electrode material has good consistency.
[0077] In some embodiments, the morphology of the nickel manganese oxide precursor includes nanoscale spherical particles and / or nanoscale quasi-spherical particles. As a preferred embodiment, the morphology of the oxide precursor is that the quasi-spherical particles are elliptical particles. This morphology is more fully in contact with the lithium source during a single sintering process, and the positive electrode obtained by sintering has better uniformity.
[0078] In some embodiments, the D50 of the nickel manganese oxide precursor is 3 μm-4 μm, such as 3 μm, 3.2 μm, 3.5 μm, 3.6 μm, 3.8 μm, 4.0 μm, etc. The positive electrode particles sintered from the small particle precursor have a smaller particle size, and the smaller particle size makes the Li + The migration path becomes shorter, and better rate performance can be achieved.
[0079] In some embodiments, the D50 of the lithium source is 5 μm-10 μm; for example, 5 μm, 7 μm, 8 μm, 10 μm, etc. When the lithium source within this particle size range is mixed and sintered with the precursor, the obtained positive electrode has good uniformity and no element segregation occurs. The lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium sulfate, and lithium nitrate.
[0080] In some embodiments, the molar ratio of the nickel manganese oxide precursor to the lithium source is 1:(1.02-1.12), such as 1:1.02, 1:1.03, 1:1.05, 1:1.08, 1:1.09, 1:1.0, 1:1.11, 1:1.12, etc. The above molar ratio can ensure the amount of lithium source required for sintering without causing excessive residual alkali.
[0081] In some embodiments, the first sintering is performed under the condition of introducing air, and the air introduction flow rate can be limited to 2L / min-5L / min, such as 2L / min, 3L / min, 4L / min, 5L / min, etc. Stable sintering can be performed under this air introduction flow rate.
[0082] In some embodiments, the temperature of the first sintering is 900°C-950°C, for example, 900°C, 920°C, 940°C, 950°C, etc.; the time of the first sintering is 12h-20h, for example, 12h, 15h, 16h, 18h, 20h, etc.
[0083] In some embodiments, the first sintering is performed at a heating rate of 3°C / min-8°C / min to 900°C-950°C; for example, 3°C / min, 5°C / min, 6°C / min, 8°C / min, etc. The first sintering can be performed stably by using this sintering process, and the particle size D50 of the lithium nickel manganese oxide sintered material obtained by using the above preparation conditions is 3μm-10μm; for example, 3μm, 4μm, 6μm, 7μm, 8μm, 10μm, etc. The lithium nickel manganese oxide of this particle size can achieve better coating of the surfactant.
[0084] In some embodiments, the chemical formula of the lithium nickel manganese oxide sintering material is Li a Ni 1-x Mn x O2, where 0.95≤a≤1.1, 0.05≤x≤0.5.
[0085] In some embodiments, the second sintering is carried out under the condition of air introduction. The flow rate of air introduction is 2L / min-5L / min; for example, 2L / min, 3L / min, 4L / min, 5L / min, etc. The temperature of the second sintering is 450℃-650℃. If the temperature is lower than 450℃, the bonding between the coating layer and the positive electrode material will be poor and the coating will be unstable; if the temperature is higher than 650℃, the coating elements will diffuse seriously and the lithium-nickel mixing may be aggravated, thereby reducing the effect of improving the cycle stability. It is preferably 450℃-650℃, for example, 450℃, 480℃, 510℃, 530℃, 560℃, 600℃, 620℃, 630℃, 650℃, etc. The time of the second sintering is 3-8h, for example, 3h, 4h, 5h, 7h, 8h, etc.
[0086] In some embodiments, the second sintering is performed by heating the temperature to 450°C-650°C at a heating rate of 3-8°C / min, such as 3°C / min, 5°C / min, 6°C / min, 8°C / min, etc. This heating rate facilitates stable sintering.
[0087] In a third aspect of the embodiments of the present application, a lithium-ion battery is provided, comprising the lithium nickel manganese oxide positive electrode material of the first aspect of the present application or the lithium nickel manganese oxide positive electrode material obtained by the preparation method of the second aspect of the present application. The positive electrode of the lithium-ion battery uses the lithium nickel manganese oxide positive electrode material of the above embodiments of the present application, which can significantly improve the first efficiency of the material, reduce the growth rate of DCR during the cycle, and improve its cycle stability. Therefore, the lithium-ion battery provided in the embodiments of the present application has good cycle stability and a high first efficiency.
[0088] In a fourth aspect of the embodiment of the present application, an electric device is provided, the electric device comprising the lithium ion battery of the third aspect of the present application. The electric device comprises the lithium ion battery provided in the embodiment of the present application, so that the electric device has good cycle stability.
[0089] The following describes the invention in conjunction with specific embodiments.
[0090] Example 1
[0091] Step 1: Set the specific surface area to 12m 2 / g, Ni with a particle size D50 of 3.6μm 0.75 Mn 0.25O oxide precursor (elliptical particles) and lithium carbonate with an average particle size D50 of 8 μm were uniformly mixed at a molar ratio of Li: oxide precursor = 1.06:1, and the mixed material was placed in a muffle furnace for the first sintering. Dry air was continuously introduced during the sintering process, and the air flow rate was controlled to be 3 L / min. The temperature was increased from 25°C (room temperature) to 930°C at a heating rate of 5°C / min, and the sintering was maintained for 12 hours. After the sintering was completed, the material was naturally cooled to room temperature, the material was taken out, and quickly transferred to an environment with a humidity of less than 5%. The material was ground and sieved to obtain Li 1.0 Ni 0.75 Mn 0.25 O2 sintering material;
[0092] Step 2: Li with a mass ratio of 100:6.5 1.0 Ni 0.75 Mn 0.25 The O2 sintering material is mixed with ammonium niobium oxalate, and the mixture is placed in a muffle furnace for a second sintering. Dry air is continuously introduced during the sintering process, and the air flow rate is controlled to be 3L / min. The temperature is increased to 650°C at a heating rate of 5°C / min and sintered for 8 hours. After the sintering is completed, the material is naturally cooled to room temperature and then taken out and quickly transferred to an environment with a humidity of less than 5%. The material is ground and sieved to obtain a lithium nickel manganese oxide positive electrode material, which is recorded as A1.
[0093] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Example 1 is: Li 1.0 Ni 0.73 Mn 0.24 Nb 0.03 O2, with a specific surface area of 1.2m 2 / g, the average particle size D50 is 4μm, the diameter distance is 1.4, and the thickness of the coating layer is 5nm.
[0094] The SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 1 at a magnification of 20K is as follows: Figure 1 As shown;
[0095] The SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 1 at a magnification of 30K is as follows: Figure 2 As shown;
[0096] The SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 1 at a magnification of 40K is as follows: Figure 3 As shown;
[0097] from Figures 1 to 3 It can be seen that there is an obvious "coral-like" structure on the surface of a single particle of the lithium nickel manganese oxide positive electrode material prepared in Example 1.
[0098] The surface energy spectrum test results of different points of the cobalt-free positive electrode material prepared in Example 1 are as follows: Figure 4 , Figure 5 As shown, from Figure 4 and Figure 5 It can be seen that the abundance of Nb element is different in different areas and is concentrated on the channel surface.
[0099] The surface energy spectrum scanning test (Nb element) result of the lithium nickel manganese oxide positive electrode material prepared in Example 1 is as follows: Figure 6 As shown, from Figure 6 It can be seen that the distribution abundance of Nb element in different areas on the surface of positive electrode material particles is different, and it is concentrated on the channel surface.
[0100] Example 2
[0101] Example 2 In the process of preparing lithium nickel manganese oxide positive electrode material, niobium oxide is used to replace ammonium niobium oxalate, and Li a Ni 1- x Mn x The mass ratio of O2 sintering material to niobium oxide is 100:6, and the remaining operating steps are the same as those in Example 1.
[0102] Specifically:
[0103] Step 1: Set the specific surface area to 12m 2 / g, Ni with a particle size D50 of 3.6μm 0.75 Mn 0.25 O oxide precursor (elliptical particles)) and lithium carbonate with an average particle size D50 of 8 μm are uniformly mixed according to a molar ratio of Li: oxide precursor = 1.06:1, and the mixed material is placed in a muffle furnace for the first sintering. Dry air is continuously introduced during the sintering process, and the air flow rate is controlled to be 3 L / min. The temperature is increased from 25°C (room temperature) to 930°C at a heating rate of 5°C / min, and the temperature is kept for 12 hours. After the sintering is completed, the material is naturally cooled to room temperature, the material is taken out, and quickly transferred to an environment with a humidity of less than 5%. The material is ground and sieved to obtain Li 1.0 Ni 0.75 Mn 0.25 O2 sintering material;
[0104] Step 2: Li with a mass ratio of 100:6 1.0 Ni 0.75 Mn 0.25The O2 sintering material is mixed with niobium oxide, and the mixture is placed in a muffle furnace for a second sintering. Dry air is continuously introduced during the sintering process, and the air flow rate is controlled to be 3L / min. The temperature is increased to 650°C at a heating rate of 5°C / min and sintered for 8 hours. After the sintering is completed, the material is naturally cooled to room temperature and then taken out and quickly transferred to an environment with a humidity of less than 5%. The material is ground and sieved to obtain a lithium nickel manganese oxide positive electrode material, which is recorded as A2.
[0105] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Example 2 is: Li 1.0 Ni 0.73 Mn 0.23 Nb 0.04 O2, with a specific surface area of 1.10m 2 / g, the average particle size D50 is 4.1μm, the diameter distance is 1.5, and the thickness of the coating layer is 4.5nm.
[0106] The SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 2 at a magnification of 20K is as follows: Figure 7 As shown;
[0107] from Figure 7 It can be seen that there is an obvious "coral-like" structure on the surface of a single particle of the lithium nickel manganese oxide positive electrode material prepared in Example 2.
[0108] Example 3
[0109] Example 3 In the process of preparing lithium nickel manganese oxide positive electrode material, aluminum oxide is used to replace ammonium niobium oxalate, and Li a Ni 1- x Mn x The mass ratio of O2 sintering material to alumina is 100:1.7; the remaining operating steps are the same as those in Example 1.
[0110] Specifically:
[0111] Step 1: Set the specific surface area to 12m 2 / g, Ni with a particle size D50 of 3.6μm 0.75 Mn 0.25 O oxide precursor (elliptical particles) and lithium carbonate with an average particle size D50 of 8 μm were uniformly mixed at a molar ratio of Li: oxide precursor = 1.06:1, and the mixed material was placed in a muffle furnace for the first sintering. Dry air was continuously introduced during the sintering process, and the air flow rate was controlled to be 3 L / min. The temperature was increased from 25°C (room temperature) to 930°C at a heating rate of 5°C / min, and the temperature was kept for 12 hours. After the sintering was completed, the material was naturally cooled to room temperature, the material was taken out, and quickly transferred to an environment with a humidity of less than 5%, and the material was ground and sieved to obtain Li 1.0Ni 0.75 Mn 0.25 O2 sintering material;
[0112] Step 2: Li with a mass ratio of 100:1.7 1.0 Ni 0.75 Mn 0.25 The O2 sintering material is mixed with alumina, and the mixture is placed in a muffle furnace for a second sintering. Dry air is continuously introduced during the sintering process, and the air flow rate is controlled at 3L / min. The temperature is increased to 650°C at a heating rate of 5°C / min and sintered for 8 hours. After the sintering is completed, the material is naturally cooled to room temperature and then taken out and quickly transferred to an environment with a humidity of less than 5%. The material is ground and sieved to obtain a lithium nickel manganese oxide positive electrode material, which is recorded as A3.
[0113] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Example 3 is: Li 1.0 Ni 0.73 Mn 0.24 Al 0.03 O2, specific surface area is 0.8m 2 / g, the average particle size D50 is 3.8μm, the diameter distance is 1.6, and the thickness of the coating layer is 1.2nm.
[0114] The SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 3 at a magnification of 20K is as follows: Figure 8 As shown;
[0115] from Figure 8 It can be seen that the surface of a single particle of the lithium nickel manganese oxide positive electrode material prepared in Example 3 has an obvious "coral-like" structure.
[0116] Example 4
[0117] In the process of preparing the lithium nickel manganese oxide positive electrode material in Example 4, the temperature of the second sintering is 600° C., and the remaining operating steps are the same as those in Example 1.
[0118] Specifically:
[0119] Step 1: Set the specific surface area to 12m 2 / g, Ni with a particle size D50 of 3.6μm 0.75 Mn 0.25O oxide precursor (elliptical particles) and lithium carbonate with an average particle size D50 of 8 μm were uniformly mixed at a molar ratio of Li: oxide precursor = 1.06:1, and the mixed material was placed in a muffle furnace for the first sintering. Dry air was continuously introduced during the sintering process, and the air flow rate was controlled to be 3 L / min. The temperature was increased from 25°C (room temperature) to 930°C at a heating rate of 5°C / min, and the sintering was maintained for 12 hours. After the sintering was completed, the material was naturally cooled to room temperature, the material was taken out, and quickly transferred to an environment with a humidity of less than 5%, and the material was ground and sieved to obtain Li 1.0 Ni 0.75 Mn 0.25 O2 sintering material;
[0120] Step 2: Li with a mass ratio of 100:6.5 1.0 Ni 0.75 Mn 0.25 The O2 sintering material is mixed with ammonium niobium oxalate, and the mixture is placed in a muffle furnace for a second sintering. Dry air is continuously introduced during the sintering process, and the air flow rate is controlled to be 3L / min. The temperature is increased to 600°C at a heating rate of 5°C / min and sintered for 8 hours. After the sintering is completed, the material is naturally cooled to room temperature and then taken out and quickly transferred to an environment with a humidity of less than 5%. The material is ground and sieved to obtain a lithium nickel manganese oxide positive electrode material, which is recorded as A4.
[0121] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Example 4 is: Li 1.0 Ni 0.73 Mn 0.23 Nb 0.04 O2, with a specific surface area of 1.1m 2 / g, the average particle size D50 is 4.1μm, the diameter distance is 1.3, and the thickness of the coating layer is 4.6nm.
[0122] The SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 4 at a magnification of 20K is as follows: Fig. 9 As shown;
[0123] from Fig. 9 It can be seen that the surface of a single particle of the lithium nickel manganese oxide positive electrode material prepared in Example 4 has an obvious "coral-like" structure.
[0124] Example 5
[0125] In the process of preparing the lithium nickel manganese oxide positive electrode material in Example 5, the second sintering time is 6 hours, and the remaining operation steps are the same as those in Example 1.
[0126] Specifically:
[0127] Step 1: Set the specific surface area to 12m 2 / g, Ni with a particle size D50 of 3.6μm 0.75 Mn 0.25 O oxide precursor (elliptical particles) and lithium carbonate with an average particle size D50 of 8 μm were uniformly mixed at a molar ratio of Li: oxide precursor = 1.06:1, and the mixed material was placed in a muffle furnace for the first sintering. Dry air was continuously introduced during the sintering process, and the air flow rate was controlled to be 3 L / min. The temperature was increased from 25°C (room temperature) to 930°C at a heating rate of 5°C / min, and the sintering was maintained for 12 hours. After the sintering was completed, the material was naturally cooled to room temperature, the material was taken out, and quickly transferred to an environment with a humidity of less than 5%. The material was ground and sieved to obtain Li 1.0 Ni 0.75 Mn 0.25 O2 sintering material;
[0128] Step 2: Li with a mass ratio of 100:6.5 1.0 Ni 0.75 Mn 0.25 The O2 sintering material is mixed with ammonium niobium oxalate, and the mixture is placed in a muffle furnace for a second sintering. Dry air is continuously introduced during the sintering process, and the air flow rate is controlled to be 3L / min. The temperature is increased to 650°C at a heating rate of 5°C / min and sintered for 6 hours. After the sintering is completed, the material is naturally cooled to room temperature and then taken out and quickly transferred to an environment with a humidity of less than 5%. The material is ground and sieved to obtain a lithium nickel manganese oxide positive electrode material, which is recorded as A5.
[0129] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Example 5 is: Li 1.0 Ni 0.73 Mn 0.23 Nb 0.04 O2, with a specific surface area of 1.1m 2 / g, the average particle size D50 is 4.1μm, the diameter distance is 1.5, and the thickness of the coating layer is 4.7nm.
[0130] The SEM image of the lithium nickel manganese oxide positive electrode material prepared in Example 5 at a magnification of 20K is as follows: Fig.10 As shown;
[0131] from Fig.10 It can be seen that the surface of a single particle of the lithium nickel manganese oxide positive electrode material prepared in Example 5 has an obvious "coral-like" structure.
[0132] Comparative Example 1
[0133] The difference between Comparative Example 1 and Example 1 is that in the process of preparing the lithium nickel manganese oxide positive electrode material in Comparative Example 1, only the first sintering is performed, and the product obtained by the first sintering is not mixed with a surfactant for the second sintering.
[0134] Specifically:
[0135] The specific surface area is 12m 2 / g, Ni with a particle size D50 of 3.6μm 0.75 Mn 0.25 O oxide precursor (elliptical particles) and lithium carbonate with an average particle size D50 of 8 μm were uniformly mixed at a molar ratio of Li: oxide precursor = 1.06:1, and the mixed material was placed in a muffle furnace for the first sintering. Dry air was continuously introduced during the sintering process, and the air flow rate was controlled to be 3 L / min. The temperature was increased from 25°C (room temperature) to 930°C at a heating rate of 5°C / min, and the temperature was kept for 12 hours. After the sintering was completed, the material was naturally cooled to room temperature, the material was taken out, and quickly transferred to an environment with a humidity of less than 5%, and the material was ground and sieved to obtain Li 1.0 Ni 0.75 Mn 0.25 O2 sintering material, denoted as B1.
[0136] Comparative Example 2
[0137] The difference between Comparative Example 2 and Example 1 is that in the process of preparing the lithium nickel manganese oxide positive electrode material in Comparative Example 2, boric acid is used instead of the surfactant ammonium niobium oxalate, and the remaining operating steps are the same as those in Example 1.
[0138] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 2 is: Li 1.0 Ni 0.73 Mn 0.24 B 0.03 O2, denoted as B2.
[0139] Comparative Example 3
[0140] The difference between Comparative Example 3 and Example 1 is that the temperature of the second sintering in the process of preparing the lithium nickel manganese oxide positive electrode material in Comparative Example 3 is 800° C., and the remaining operating steps are the same as those in Example 1.
[0141] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 3 is: Li 1.0 Ni 0.73 Mn 0.24 Nb 0.03 O2, recorded as B3.
[0142] Comparative Example 4
[0143] The difference between Comparative Example 4 and Example 1 is that no surfactant is added during the preparation of the lithium nickel manganese oxide positive electrode material in Comparative Example 4, and the remaining operating steps are the same as those in Example 1.
[0144] The chemical formula of the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 4 is: Li 1.0 Ni 0.75 Mn 0.25 O2, recorded as B4.
[0145] Electrochemical performance study of the lithium nickel manganese oxide positive electrode materials prepared in Examples 1-5 and Comparative Examples 1-4 of the present application:
[0146] Test method: The nickel manganese oxide positive electrode material, conductive carbon and polyvinylidene fluoride (PVDF) prepared in Examples 1-5 and Comparative Examples 1-4 were mixed in a mass ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone (NMP) was added to make the slurry solid content 41%-50%, and mixed evenly in a high-energy planetary mixer to obtain a uniform slurry with appropriate viscosity. The slurry was coated on aluminum foil with an automatic coating machine (the scraper height was 41μm), and the electrode was first placed in a 120℃ blast drying oven to remove the surface NMP solution, and then dried in a 100℃ vacuum drying oven overnight. The dried electrode pieces were hot pressed (the temperature and pressure of the hot pressing were 100°C and 700kg respectively) and cut to obtain positive electrode discs with a diameter of 12mm and a thickness of 60-61μm. Lithium metal was used as the negative electrode and 1M lithium hexafluorophosphate carbonate solution was used as the electrolyte. They were assembled into button cells in a glove box with a water and oxygen content of less than 0.5ppm, and constant current charge and discharge cycle tests were carried out on a Xinwei battery tester.
[0147] The charge and discharge test conditions are: test temperature 45°C, charge and discharge rate 0.5C, charge and discharge cut-off voltage 3.0-4.4V (vs Li+ / Li), and 50 cycles;
[0148] Among them, the calculation method of the first effect is: first discharge capacity / first charge capacity*100%;
[0149] The calculation method of 50-cycle capacity retention rate is: (discharge specific capacity after 50 charge and discharge cycles / discharge specific capacity in the first cycle)*100%;
[0150] The calculation method of DCR for the first discharge cycle is: assuming that the initial discharge voltage is V1 (in volts), the voltage after 1 minute of constant current discharge is V2 (in volts), the discharge current is I (in amperes), DCR = (V1-V2) / I;
[0151] The calculation method of the DCR growth rate after 50 cycles is: assuming that the DCR of the first cycle is R1 and the DCR of the 50th cycle is R2, the growth rate = (R1-R2) / R1*100%;
[0152] The above test results are shown in Table 1:
[0153] Table 1 Electrochemical properties of lithium ion button cells assembled with positive electrode materials prepared in Examples and Comparative Examples
[0154]
[0155] Note: DCR refers to the DC internal resistance of the battery, which represents the ratio of the battery voltage change to the corresponding discharge current change under working conditions.
[0156] The first effect refers to the ratio of the first discharge capacity of the battery to the first charge capacity, usually expressed as a percentage. The size of the first effect can reflect the reversibility of the active ions embedded in the crystal lattice. The higher the first effect, the higher the reversibility.
[0157] It can be seen from Table 1 that the performance data analysis of the lithium nickel manganese oxide positive electrode material prepared by Example 1 and the lithium nickel manganese oxide positive electrode material prepared by Comparative Example 1 shows that after the layered oxide positive electrode material and the surfactant are fused with each other, heat treatment is performed within an appropriate temperature range, which can significantly improve the initial efficiency of the material, reduce the growth rate of DCR during the cycle, and improve its cycle stability.
[0158] Through the performance data analysis of the lithium nickel manganese oxide positive electrode material prepared in Example 1 and the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 2, it can be seen that the selection of surfactant is a key factor affecting the positive electrode material. The material in the coating layer contained in the surfactant can act as a physical barrier between the positive electrode material and the electrolyte, stabilize the interface, block the dissolution of metal ions and effectively prevent the collapse of the surface structure of the active material, improve electronic conductivity, improve stability, and expand Li + Embedding / extraction channels and reducing the degree of cation mixing can improve the electrochemical performance of the positive electrode material.
[0159] From the performance data analysis of the lithium nickel manganese oxide positive electrode material prepared in Example 1 and the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 3, it can be seen that if the sintering temperature of the second sintering is higher than 650°C, the initial effect and stability of the obtained product will be significantly reduced, that is, the sintering temperature of the second sintering is the key factor affecting the positive electrode material.
[0160] From the performance data analysis of the lithium nickel manganese oxide positive electrode material prepared in Example 1 and the lithium nickel manganese oxide positive electrode material prepared in Comparative Example 4, it can be seen that the addition of the surfactant during the second sintering process can significantly improve the initial efficiency and stability of the positive electrode material.
[0161] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A lithium nickel manganese oxide positive electrode material, characterized in that: The positive electrode material includes a lithium nickel manganese oxide layered oxide and a coating layer coated on the surface of the lithium nickel manganese oxide layered oxide, wherein the coating layer has a coral-like structure; the material in the coating layer is selected from one or more of Al, Ti, Zr and Nb.
2. The lithium nickel manganese oxide positive electrode material according to claim 1, characterized in that The general chemical formula of the lithium nickel manganese oxide positive electrode material is Li a Ni 1-x-y Mn x M y O2, wherein: 0.95≤a≤1.1, 0.05≤x≤0.5, 0.01≤y≤0.1, M is selected from one or more of Al, Ti, Zr, and Nb.
3. The lithium nickel manganese oxide positive electrode material according to claim 1 or 2, characterized in that: The specific surface area of the lithium nickel manganese oxide positive electrode material is 0.4 m 2 / g-1.5m 2 / g; And / or, the D50 of the lithium nickel manganese oxide positive electrode material is 1.5 μm-5.5 μm; And / or, the diameter distance of the lithium nickel manganese oxide positive electrode material is 1.0-2.0; And / or, the coating layer contained in the lithium nickel manganese oxide positive electrode material has a thickness of 0.1 nm-10 nm.
4. A method for preparing a lithium nickel manganese oxide positive electrode material, characterized in that: The following steps are involved: The nickel manganese oxide precursor is mixed with a lithium source and sintered for the first time to obtain a nickel manganese oxide lithium sintered material; The lithium nickel manganese oxide sintering material is mixed with a surfactant and sintered for a second time to obtain the lithium nickel manganese oxide positive electrode material.
5. The preparation method according to claim 4, characterized in that: The surfactant is selected from one or more of ammonium niobium oxalate, niobium oxide, aluminum oxide, zirconium oxide, and titanium oxide; And / or, the mass ratio of the lithium nickel manganese oxide sintered material to the surfactant is 100:(1-7).
6. The preparation method according to claim 4 or 5, characterized in that: The chemical formula of the nickel manganese oxide precursor is Ni 1-x Mn x O2, where 0.05≤x≤0.5; And / or, the specific surface area of the nickel manganese oxide precursor is 5m 2 / g-15m 2 / g; and / or, the morphology of the nickel manganese oxide precursor includes nanoscale spherical particles and / or nanoscale spherical-like particles; And / or, the nickel manganese oxide precursor D50 is 3 μm-4 μm; And / or, the D50 of the lithium source is 5 μm-10 μm; And / or, the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, lithium sulfate and lithium nitrate; And / or, the molar ratio of the nickel manganese oxide precursor to the lithium source is 1:(1.02-1.12).
7. The preparation method according to claim 4 or 5, characterized in that: The first sintering is carried out under the condition of introducing air, and the flow rate of the introduced air is 2L / min-5L / min; And / or, the temperature of the first sintering is 900° C.-950° C., and the time of the first sintering is 12 h-20 h; And / or, the first sintering is performed by heating the temperature to 900°C-950°C at a heating rate of 3°C / min-8°C / min; And / or, the chemical formula of the lithium nickel manganese oxide sintering material is Li a Ni 1-x Mn x O2, where 0.95≤a≤1.1, 0.05≤x≤0.5; And / or, the D50 of the lithium nickel manganese oxide sintered material is 3 μm-10 μm.
8. The preparation method according to claim 4 or 5, characterized in that: The second sintering is carried out under the condition of introducing air, and the flow rate of the introduced air is 2L / min-5L / min; And / or, the temperature of the second sintering is 450°C-650°C, and the time of the second sintering is 3h-8h; And / or, the second sintering is performed by heating the temperature to 450°C-650°C at a heating rate of 3°C / min-8°C / min.
9. A lithium ion battery, characterized in that: It comprises the lithium nickel manganese oxide positive electrode material as described in any one of claims 1 to 3 or the lithium nickel manganese oxide positive electrode material obtained by the preparation method of any one of claims 4 to 8.
10. An electrical device, characterized in that: The electrical device comprises the lithium-ion battery according to claim 9.
Citation Information
Cited By
A high-safety nickel cobalt manganese lithium oxide semi-solid-state battery and its preparation method
CN119864515B
